Defining the Integration Capacity of Embryonic Stem Cell‐Derived Photoreceptor Precursors123. (18th June 2012) - West, Emma L.; Gonzalez‐Cordero, Anai; Hippert, Claire; Osakada, Fumitaka; Martinez‐Barbera, Juan Pedro; Pearson, Rachael A.; Sowden, Jane C.; Takahashi, Masayo; Ali, Robin R.
Abstract: Retinal degeneration is a leading cause of irreversible blindness in the developed world. Differentiation of retinal cells, including photoreceptors, from both mouse and human embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), potentially provide a renewable source of cells for retinal transplantation. Previously, we have shown both the functional integration of transplanted rod photoreceptor precursors, isolated from the postnatal retina, in the adult murine retina, and photoreceptor cell generation by stepwise treatment of ESCs with defined factors. In this study, we assessed the extent to which this protocol recapitulates retinal development and also evaluated differentiation and integration of ESC‐derived retinal cells following transplantation using our established procedures. Optimized retinal differentiation via isolation of Rax.GFP retinal progenitors recreated a retinal niche and increased the yield of Crx + and Rhodopsin + photoreceptors. Rod birth peaked at day 20 of culture and expression of the early photoreceptor markers Crx and Nrl increased until day 28. Nrl levels were low in ESC‐derived populations compared with developing retinae. Transplantation of early stage retinal cultures produced large tumors, which were avoided by prolonged retinal differentiation (up to day 28) prior to transplantation. Integrated mature photoreceptors were not observed in the adult retina, even when more than 60% of transplanted ESC‐derived cells expressed Crx. We conclude that exclusion of proliferative cells from ESC‐derived cultures is essential for effective transplantation. Despite showing expression profiles characteristic of immature photoreceptors, the ESC‐derived precursors generated using this protocol did not display transplantation competence equivalent to precursors from the postnatal retina. Stem Cells 2012;30:1424–1435